BUSINESS INTELLIGENCE FOR INSURANCE COMPANIES - A. Ignatiuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The current state and future trends for the world and domestic insurance markets are analyzed. The description of business intelligence methodology, tools and their practical implication for insurance companies are provided.